2020
DOI: 10.1519/jsc.0000000000002833
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Menthol on Recovery From Exercise-Induced Muscle Damage

Abstract: Gillis, DJ, Vellante, A, Gallo, JA, and D'Amico, AP. Influence of menthol on recovery from exercise-induced muscle damage. J Strength Cond Res XX(X): 000-000, 2018-This study assessed the influence of menthol, a cold receptor agonist, on recovery from exercise-induced muscle damage (EIMD). Forty-seven healthy males were allocated to a Control (CON, n = 18), Placebo (P, n = 14), or 4.0% Menthol (M, n = 15) condition. Participants were familiarized with a testing battery (TB) including: perception of lower-body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 34 publications
2
15
0
Order By: Relevance
“…More importantly, their study focused on menthol-based cream. Their findings were supported by a recent study [35] that reported the effectiveness of methanol in promoting strength recovery after exercise-induced muscle damage.…”
Section: Discussionsupporting
confidence: 69%
“…More importantly, their study focused on menthol-based cream. Their findings were supported by a recent study [35] that reported the effectiveness of methanol in promoting strength recovery after exercise-induced muscle damage.…”
Section: Discussionsupporting
confidence: 69%
“…Practically, this may partially explain both Meamarbashi [ 15 ] and our findings, whereby a single dose of menthol may prove effective, but repeated application may act to inhibit contractile or associated enzymatic activity. It should be noted that this mechanism has also been proffered as an explanation for menthol’s analgesic effect [ 40 ], with alterations in regional cutaneous blood flow also observed [ 39 ], thus warranting investigation into repeated topical application of menthol during strength and power performance, beyond the work already conducted in facilitating recovery [ 41 , 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Menthol can be applied topically via creams, gels, or sprays [ 6 , 8 , 13 , 29 , 31 , 32 , 44 ], with timing of administration altered to suit the aim of the exercise bout and nature of menthol topical application. For instance, menthol applied as a spray prior to or repeatedly throughout an exercise bout has been shown to improve thermal comfort and sensation, but may alter athletes’ sweat rate [ 8 , 29 , 30 , 44 ], potentially presenting a conflict in thermoregulatory drives.…”
Section: Introductionmentioning
confidence: 99%